Depiction of a Ghatapallava motif on the pillar shaft - Temples of India Project Team (Jio Institute, 2024)
Remains of pilasters from the vicinity of the Neelkanth Mahadev Temple. The original position is not known, but these are stylistically similar to the interior of Neelkanth Mahadev Temple. The pillar shaft has a ghatapallava (pot with foliage) motif.